Twenty years of emotional-behavioral problems of community adolescents living in Italy measured through the Achenbach system of empirically based assessment (ASEBA): a systematic review and meta-analysis - Pace, Cecilia Serena; Muzi, Stefania; Frigerio, Alessandra; Morganti, Wanda; Bianchi, Victoria; Rogier, Guyonne (Frontiers in Psychiatry, 2023)
Background This is a systematic review and meta-analysis of emotional and behavioral problems among Italian community adolescents in the last 20 years, as assessed through the ASEBA questionnaires CBCL 6–18, YSR 11–18 and TRF 6–18. Research questions address: (1) pooled means of problems’ scores in questionnaires scales; (2–3) variations in scores according to sociodemographic and time-related factors, and studies’ quality; (4) trends in research with ASEBA instruments along with other outcomes, e.g., psychopathological symptoms. Methods A systematic literature review of Scopus, EBSCO, PubMed, Web of Science, and ProQuest databases using the PRISMA 2020 guidelines was conducted on November, 2021, and of grey literature on December, 2021. The quality of studies was assessed through the Newcastle-Ottawa Scale. Results Forty-four studies were eligible for the systematic review, of which 34 were included for meta-analysis. Results showed that: (1) emotional-behavioral problems were higher when assessed by the CBCL and lower when assessed by the YSR compared to normative data; (2) there were no gender and age differences, except for higher scores of Anxious/Depression symptoms, in girls. (3) internalizing and attention problems increased over the last two decades. (4) major trends of Italian research investigate adolescents’ emotional behavioral problems concerning attachment, comorbid symptoms, especially internet addictions, and eating disorders. Discussion Despite some limitations (e.g., low-medium quality of most studies, no data on the TRF, under-representation of some geographical areas, some search-related choices), these data provides Italian practitioners and international researchers of some parameter to evaluate Italian adolescents emotional-behavioral problems. Registered on PROSPERO N. CRD42022299999.